Unlocking mhGAP and family medicine potential: Strategic solutions for Indonesian mental health integration - Putu Aryani; Pande Putu Januraga; Manik Jantine Djelantik; Shailendra Prasad (Universitas Udayana, 2025)
Mental health has become a critical global concern in 2025, influencing individuals, communities, and healthcare systems worldwide. Recognizing its significance is essential for fostering well-being and resilience across all aspects of life. The World Health Organization emphasizes that mental health is a basic human right and essential for both personal growth and societal progress. It empowers individuals to handle life’s difficulties, tap into their potential, learn effectively, perform well in their tasks, and make meaningful contributions to their communities1. Global threats to mental health today include economic and social inequalities; public health emergencies (including COVID-19); humanitarian emergencies (including conflict and forced displacement); and the climate crisis2. Mental health is closely linked to physical health. However, the relationship between mental health and physical disease tends to be neglected by communities as well as health care providers, specifically in Low Middle-Income Countries (LMICs)3. The vast majority of patients with mental disorder in LMICs have limited access to proper treatment 4. In contrast, European region countries (EUR) report the highest rate of mental health treatment compared to other regions5. Undetected mental disorders increased the risky behaviors related to chronic diseases, in turn, people with chronic diseases are also prone to experiencing mental health issues 6-10.